Volunteering in the Context of Medical Education: Analisys and Recommendations for Future Development - Shotarova, Zlatina (Research Papers, 2025)
This study explores the development of volunteering in medical universities in Bulgaria. Through an analysis of public information available from the universities, the benefits for both the students themselves (development of key skills, professional orientation, etc.) and for society are highlighted. The publication aims to present and analyze international good practices related to volunteering and to draw recommendations for its encouragement and promotion in educational institutions. In the article, DESK analysis, analysis of statistical data, SWOT analysis, as well as a synthesis of information from the official websites and the profiles on the social networks Facebook and Instagram at the medical universities in the country are used in order to identify the existing volunteer practices and initiatives and to analyze the way universities organize and promote volunteering among students, staff, and lecturers. A limitation of the present publication is that the analysis of the official profiles on the medical universities in the social network Facebook covers the period September 2024 – April 2025.
Keywords: Volunteering; Medical university; Social engagement; Society